An enunciative description of three concessive sentence adverbs in English: yet, however, nevertheless - Graham Ranger (Anglophonia)
Concessive constructions involve a complex operation whereby a speaker marks recognition, if not endorsement, of an inferential relationship obtaining between two states of affairs p and q, while at the same time overriding this relationship in context. Such constructions may distance the speaker from endorsement of one or other of the propositions, or indeed from the endorsement of the underlying inferential relationship. This subjective positioning, relative to the domains of p, q and the relationship between the two, is correlated with the use of specific markers, which may be further parametered in contextual configurations.In the present paper I aim to focus on three particular concessive constructions (I use the term "construction" in the broad sense of a textual configuration, implying position and context) specifically involving what are traditionally known as sentence adverbials, YET, HOWEVER and NEVERTHELESS. Each marker is described, within the metalinguistic framework of the Theory of Enunciative and Predicative Operations, as providing specific indications with respect to the construction of referential values for the related propositions and to subjective positioning. The modelisation of operations will additionally be seen to correspond to characteristic contextual configurations of each marker, which may be described on the basis of corpus evidence (specifically, the British National Corpus and a short contemporary argumentative text).